Class agency under conditions of self-enforcement: Marx on capitalists' common's problem - Korkut A. Ertürk (The University of Utah, Department of Economics, 2019)
Marx discussed institutional innovations in the context of a complex dynamic between inter versus intra-group opportunism, which contains clues for understanding how capacity for class agency develops. His lengthy discussion of the English Factory Acts in his Vol. I of Capital is an important case in point, which the paper revisits for its broader lessons not only for how institutions solve collective action problems but also how they become self-enforcing when third party enforcement is ineffective. The paper gives an account of how the Acts could have become self-enforcing at a time when the state enforcement capacity was rudimentary at best. The argument focuses on the dynamic between inter versus intra-class opportunism, shedding analytical light on how organized labor could help capitalists bolster their capacity for class agency.
Keywords: B14; B55; C72; 330; institutions; collective action problem; opportunistism; common's problem